A liberdade inscrita nos sambas enredos cariocas (1943 a 2013) - Adalgimar Gomes Goncalves (2016)
Drawing on a collection of 232 carioca samba plots, this study carries out an analysis of the word freedom inscribed in these compositions, investigating they ways in which this word took on several meanings in multiple contexts and considering these productions from the perspective of intertextuality in the realm of literature. Rio de Janeiro was chosen because it is where the first samba schools ("escolas de samba") emerged, as well as where the consolidation of Brazilian carnival took place. Aside from approaching in a few lines the origin of carnival, from the first agrarian rituals as far as the formation of samba schools (escolas de samba), this study examined the period from 1943 to 2013, where it was possible to confirm the use of the word freedom in those written productions. Thus, the first period that was analyzed comprises the Vargas Era and the Populist Democracy (1943 to 1964), the second one is the Military Dictatorship (1965 to 1985) and the third one, the democracy (1986 to 2013). The study is also based on studies about the history of carnival, in carnavalization theories and in some anthropolical and sociological lines about the subject. Therefore, the contribution of this dissertation is to investigate lyrics as poetic production, from the perspective of a textuality that re-signifies discourses from literature, culture, memory and, especially, Brazilian history, departing from the carnival composers writings, from different times, under the prism of freedom.